Taguchi method statistical analysis on characterization and optimization of 18- nm double gate MOSFETs - Abdul Hamid, Afifah Maheran; Mogan, Pritigavane; Mohd Nizam, Nur Hazwani Naili; Salehuddin, Fauziyah; Sabani, Norhayati (Universiti Malaysia Perlis, 2024)
A bi-layer graphene with a multigate structure was intensified and analysed on an 18-nm Metal Oxide Semiconductor Field-Effect Transistor (MOSFET) device to obtain an optimal performance parameter. The device has a gate structure made of Titanium Dioxide (TiO2) that serves as a high-k material and a metal gate made of Tungsten Silicide (WSix). The Silvaco TCAD Software which are ATHENA and ATLAS modules were used to enhance the fabrication process of virtual devices and to verify the electrical properties of a specific device. According to the International Technology Roadmap Semiconductor (ITRS) specifications of 0.179 V ± 12.7% for threshold voltage (VTH) and 20 nA/m for leakage current (ILEAK), the Taguchi L9 orthogonal array strategy was used to improve the device process parameters for optimum VTH and ILEAK. For the NMOS device, the process parameter of VTH Adjust Implant Dose was used as the dominant factor while Source/Drain (S/D) Implant Energy was used as the adjustment factor whereby for PMOS device, S/D Implant Energy was the dominant factor while S/D Implant Tilt was the adjustment factor in order to achieve a robust design through the Taguchi method implementation. The percentage affecting the process parameter is then applied to the results of the signal to noise ratio (SNR) of Nominal-the-best (NTB) for VTH and Smaller-the-better (STB) for ILEAK.